From Offline to Online: Utilizing Sentiment and Web Analytics to Navigate Retail Transformation - Agustin, Bayani Krisanto; Ting, Alon Dakila; Dolores, Althea Keenan (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
The covid-19 pandemic has forced the way businesses run, including the offline apparel store that needs to shift their business to an online shopping platform. This also means that the volume of unstructured data that needs to be analyzed has increased significantly. This unstructured data should be analyzed accurately to help businesses in decision-making and solve their problems such as understanding customer satisfaction levels and evaluating marketing approaches. One way to utilize unstructured data is by using text analytics, the data like customer reviews from the online shopping platform and social media can be integrated and analyzed using a sentiment analysis approach in order to gain a better understanding of customer satisfaction levels. Furthermore, web analytics can also be utilized to evaluate the current marketing approach and how to maximize the marketing strategy for the business.